2005
DOI: 10.1086/429334
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Leukocytes and Elevated Cytokine Levels in Semen fromSchistosoma haematobium–Infected Individuals

Abstract: In this study, we investigated the seminal inflammatory response to egg infestation of the urogenital organs in 240 semen-donating men aged 15-49 years living in a Schistosoma haematobium-endemic area of Madagascar. In 29 subjects (12%) with excretion of > or =5 ova/ejaculate, leukocytospermia (>10(6) leukocytes/mL) and the presence of seminal lymphocytes and eosinophil leukocytes were each significantly more prevalent than in 74 subjects (31%) who were S. haematobium negative (P<.01). In addition, seminal lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 52 publications
4
63
0
Order By: Relevance
“…25 Semen of infected men frequently contains S. haematobium ova, together with increased seminal levels of leukocytes and the inflammatory cytokines interleukin (IL)-4, IL-6, IL-10, and tumor necrosis factor alpha (TNF-α). 26 These findings and ours support the hypothesis that men with urogenital schistosomiasis may more easily transmit HIV to their sexual partners due to tissue inflammation and bleeding, leading to higher concentrations of HIV in the semen of HIVschistosome coinfected men than in HIV-infected men without schistosome infection. 26,27 A recent prospective study demonstrated that men and women with the helminthic infection lymphatic filariasis had a 2-fold increased risk of incident HIV infection compared with those without filariasis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…25 Semen of infected men frequently contains S. haematobium ova, together with increased seminal levels of leukocytes and the inflammatory cytokines interleukin (IL)-4, IL-6, IL-10, and tumor necrosis factor alpha (TNF-α). 26 These findings and ours support the hypothesis that men with urogenital schistosomiasis may more easily transmit HIV to their sexual partners due to tissue inflammation and bleeding, leading to higher concentrations of HIV in the semen of HIVschistosome coinfected men than in HIV-infected men without schistosome infection. 26,27 A recent prospective study demonstrated that men and women with the helminthic infection lymphatic filariasis had a 2-fold increased risk of incident HIV infection compared with those without filariasis.…”
Section: Discussionsupporting
confidence: 87%
“…26 These findings and ours support the hypothesis that men with urogenital schistosomiasis may more easily transmit HIV to their sexual partners due to tissue inflammation and bleeding, leading to higher concentrations of HIV in the semen of HIVschistosome coinfected men than in HIV-infected men without schistosome infection. 26,27 A recent prospective study demonstrated that men and women with the helminthic infection lymphatic filariasis had a 2-fold increased risk of incident HIV infection compared with those without filariasis. 28 Unlike schistosomiasis, filariasis is not known to have direct effects on the genital tract, suggesting that systemic immune changes induced by filariasis could increase HIV susceptibility.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…4 False positive cases may be caused by the fact that S. haematobium ova can also be found in sperm and history of sexual intercourse was not recorded in this study. 22 The contamination from the outer genitals by urine or contamination from previous analyses (e.g., the practice of recycling/reusing slides/filters) was not an issue in this study.…”
Section: Discussionmentioning
confidence: 74%
“…Increased susceptibility to reinfection has also been observed [26]. Finally, female [27] (and, likely, male [28]) urogenital schistosomiasis due to S. haematobium increases the risk for HIV transmission. To date, the literature is lacking regarding significant interactions between HIV and intestinal, hepatic, or pulmonary trematodes.…”
Section: Trematodesmentioning
confidence: 99%